Bibliography and research of the press of the Communist Party of Lithuania of 1917-1940 - Žiedūnė Zaveckieenė (Knygotyra)
The press of the Communist Party of Lithuania from 1917 to 1940 holds a significant place in the history of Lithuanian press. The scope of this research is quite extensive, covering about 1,100 books and booklets, 413 periodicals, and several thousand appeals. The research on this subject began in 1947. Currently, more than 10 researchers are actively working on this topic. Hundreds of articles dedicated to this subject have been published in selected scientific works such as "Book Research" ("Knygotyra"), "The Problems of the LCP History" ("LKP istorijos klausimai"), and "Journalistics" ("Žurnalistika"). About 8 theses have been defended, but only a small portion of this material has been published—just 2 works, and not completely.